A Microstrip Monopole Antenna Design for 5G Sub-6 GHz Applications Using Deep Learning - Colak, Berker; Belen, Mehmet Ali; Kiani, Farzad; Tari, Ozlem; Mahouti, Peyman; Akgol, Oguzhan (WILEY, 2026)
This study presents the design and optimization of a microstrip monopole antenna for 5G sub-6 GHz applications, employing a deep learning-based surrogate model combined with honeybee mating optimization (HBMO). The studied antenna structure employs air via arrays, intended to enhance antenna performance, including improved impedance matching and increased bandwidth. It is important to note that, unlike conventional antennas, the proposed design does not include a fully enclosed metallic cavity similar to a substrate integrated waveguide (SIW) antenna designs. A sensitivity analysis was conducted to assess the impact of these parameters, emphasizing the need for optimal tuning. To generate training and test datasets efficiently, Latin hypercube sampling (LHS) was used. A convolutional neural network (CNN) surrogate model was trained, outperforming other machine learning (ML) algorithms in predictive accuracy and generalization. The proposed CNN-HBMO framework reduced computational costs by minimizing the need for expensive electromagnetic (EM) simulations, enabling rapid design space exploration. The optimized antenna was fabricated and validated through experimental measurements, achieving 2-3 dBi gain and S-11 < -10 dB across the 2.7-5.2 GHz band. Compared to existing designs, the proposed antenna offers a compact size (34 & times; 34 mm) with competitive performance, making it suitable for multi-band 5G applications.
Keywords: 5G; artificial intelligence; deep learning; microstrip antenna; stacked antenna; surrogate modelling; Engineering